2017
DOI: 10.1103/physreve.96.052409
|View full text |Cite
|
Sign up to set email alerts
|

Forces in inhomogeneous open active-particle systems

Abstract: We study the force that noninteracting pointlike active particles apply to a symmetric inert object in the presence of a gradient of activity and particle sources and sinks. We consider two simple patterns of sources and sinks that are common in biological systems. We analytically solve a one-dimensional model designed to emulate higher-dimensional systems, and study a two-dimensional model by numerical simulations. We specify when the particle flux due to the creation and annihilation of particles can act to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Active bursts generated by Myosin-V are fundamental for nuclear positioning in mouse oocytes. In fact, active diffusion is here thought to create pressure gradient and directional forces strong enough to induce nuclear displacements [31,160,161]. As in the earlier studies discussed above, the FDT is sharply violated at low frequencies, while it is recovered at large ones [162].…”
Section: Fluctuations Of Probe Particles Inside Living Cellsmentioning
confidence: 87%
“…Active bursts generated by Myosin-V are fundamental for nuclear positioning in mouse oocytes. In fact, active diffusion is here thought to create pressure gradient and directional forces strong enough to induce nuclear displacements [31,160,161]. As in the earlier studies discussed above, the FDT is sharply violated at low frequencies, while it is recovered at large ones [162].…”
Section: Fluctuations Of Probe Particles Inside Living Cellsmentioning
confidence: 87%
“…We showed that the activity of these actin-positive vesicles decreases from the cortex to the oocyte center as quantified by their squared velocity. On the basis of a simple model describing the pool of actin-positive vesicles as an ideal suspension of self-propelled particles, we proposed that this gradient of activity of actin vesicles, which move by active diffusion (Almonacid et al, 2015), generates an effective pressure gradient (Razin et al, 2017b,a; Solon et al, 2015) and thus a propulsion force. It would therefore be the driver of nuclear motion toward the oocyte center (Almonacid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we used analytical modeling to show that, in principle, a gradient of active particles can center objects (Razin et al, 2017b,a). Here, we used 3D numerical simulations to allow direct comparison between the model and the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Future work using better resolved imaging conditions could test this prediction. Alternatively, a system with a radial gradient in could have a roughly uniform density of vesicles (as observed 2 ) only if there are rapid processes of vesicle formation and annihilation throughout the oocyte cytoplasm 12 . The currently available data about the life-time of the vesicles is not precise enough to rule this out, and this scenario would predict that the accumulation of actin on the surface…”
Section: Comparison To Theoretical Analysis In Terms Of Active Brownimentioning
confidence: 99%
“…Accordingly, the spontaneous fluctuations, or activity of actin-positive vesicles decreases from the cortex to the oocyte center as quantified by their squared velocity v 2 . On the basis of a simple model describing the pool of actin-positive vesicles as an ideal suspension of self-propelled particles, we suggested that this gradient of activity from actin vesicles, which move by active diffusion 2 , generates an effective pressure gradient [11][12][13] and thus a propulsion force. It is thereby the trigger of the nuclear motion towards the oocyte center 14 .…”
Section: Introductionmentioning
confidence: 99%